Patient education materials: improving readability to advance health equity - Grünebaum, Amos; Pollet, Susan L.; McLeod-Sordjan, Renee; Bachman, Gloria; Chervenak, Frank A. (Journal of perinatal medicine, 2025)
To assess the readability of American College of Obstetricians and Gynecologists (ACOG) patient education pamphlets and evaluate changes over 25 years to determine their role as a social determinant of health affecting maternal health disparities. Cross-sectional descriptive analysis of 134 English-language ACOG patient pamphlets using five validated readability metrics (Flesch Reading Ease Score, SMOG Index, Gunning Fog Index, Coleman-Liau Index, and Bormuth Grade Placement). Materials were categorized into five groups: Pregnancy & Childbirth, Gynecologic Conditions, Other, Cancer & Screening, and Infections & STIs. A random subset of 20 pamphlets underwent quality assessment using the DISCERN tool. Results were compared with historical data from 1999. The mean DISCERN score was 65.6/75, indicating excellent content quality. However, readability analysis revealed concerning accessibility barriers. The mean Flesch Reading Ease score was 58.4 ± 6.2, with only 35.1 % of pamphlets meeting plain language standards (≥60 score, equivalent to 8th grade or below). Most materials (57.5 %) required 10th-12th grade reading ability. Across all readability metrics, the average grade level was 9.5, with only 2.2-6.7 % of pamphlets meeting recommended standards (≤8th grade). Comparison with 1999 data showed worsening readability, with scores increasing 1.0-3.7 grade levels across all metrics. ACOG patient education materials consistently exceed recommended readability levels and have become more complex over 25 years. This inaccessibility perpetuates health disparities, particularly affecting marginalized populations with lower health literacy. Implementing plain language policies, AI-driven text simplification, and readability audits are essential for advancing maternal health equity and ensuring all patients can access comprehensible reproductive health information.